Perilaku Kekuatan Mortar Tahan Api Dengan Bahan Tambah Gula Aren - Putri, Nanda Dwi; Olivia, Monita; Djauhari, Zulfikar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This study discusses the behavior of fire-resistant mortar strength with the addition of palm sugar. The purpose of the addition of palm sugar is to increase the fireproof mortar strength at high temperatures. Palm sugar content variation used was 0,10%, 0,30%, and 0,50% of the weight of the cement. The test object made in this study were 48 units with details of 12 pieces of mortar OPC+0,10% palm sugar, 12 pieces of mortar OPC+0,30% palm sugar, 12 pieces of mortar OPC+0,50% palm sugar, and 12 OPC mortar normal as a control. Mortar burned at a temperature of 250○C, 500○C, and 750○C for 3 h at 28 days and then tested compressive strength. The results of research and compressive strength before being burned at a temperature of 250○C showed that normal OPC has the highest compressive strength. But at a temperature of 500○C and 750○C a compressive strength of palm sugar mortarOPC+0,10% higher than normal OPC.Keywords: Mortar fire- resistant, palm sugar, OPC, compressive strength,